Focus sur les Observatoires photographiques du paysage (OPP) réalisés par le Conservatoire régional d’espaces naturels (CREN) de Poitou-Charentes - Patrick Guédon (Projets de Paysage)
Since 1994, the Conservatoire régional d’espaces naturels (CREN) of the region of Poitou-Charentes set up Photographic Observatories of the Landscape to observe and monitor changes in the natural spaces of the region. Each site in the programme comprises several observation points supplying a total of 450 series of photographs. These series are used to compile or update planning documents and are added to a regional photographic archive dedicated to natural spaces. In Poitou-Charentes, due to the rapid decline in biodiversity, the CREN is increasingly called on to intervene in support of the conservation of the region’s natural heritage. As a result, many stakeholders at the municipal and regional levels benefit from advice as well as technical support and training in setting up their own Photographic Observatories of the Landscape.